What are the consequences of a managerial approach to union renewal for union behaviour? A case study of USDAW. Issue 1 (3rd January 2017) - Evans, Samantha; Pyman, Amanda; Byford, Iona
Abstract : Purpose: The purpose of this paper is to explore the consequences of a managerial approach to renewal for a union's behaviour by analysing the UK's fourth largest trade union – The Union of Shop, Distributive and Allied Workers (USDAW). Design/methodology/approach: The findings draw on in-depth semi-structured interviews with union officials. Findings: The research findings show the significance of a managerialist approach to UDSAW's renewal strategy and its correlation with existing renewal strategies of organising and partnership. However, this approach was not immune to context, with tensions between agency and articulation challenging the basic concept of managerialism and influencing union behaviour. Research limitations/implications: The data were collected from a single case with a small sample size. Practical implications: The authors' findings suggest that tensions between bureaucracy and democracy will mediate the extent to which managerialist approaches can be used within unions adding support to the strategic choice theory and underlying arguments that unions can influence their fortune. However, institutional and external pressures could see managerialism becoming more prevalent, with oligarchic and bureaucratic forces prevailing, which could be particularly applicable to unions operating in challenging contexts, such as USDAW. The managerialisation of unions has consequences for union officers; with officers facing increasing pressure in their roles to behave as managers with attendant implications for role conflict, identity and motivation. Social implications: If managerialism is becoming more prevalent with unions, with oligarchic and bureaucratic forces prevailing, this has potentially wider societal implications, whereby collectivism and worker-led democracy could become scarcer within unions and the workplace, thus irretrievably altering the nature of the employment relationship. Originality/value: This paper brings together disparate themes in the literature to propose a conceptual framework of three key elements of managerialism: centralised strategies; performance management and the managerialisation of union roles. The authors' findings demonstrate how there is scope for unions to adopt a hybrid approach to renewal, and to draw upon their internal resources, processes and techniques to implement change, including behavioural change. Consequently, theories and empirical studies of union renewal need to better reflect the complexities of approaches that unions are now adopting and further explore these models within the agency and articulation principles that underpin the nature of unions.